Night, neon : tales of mystery and suspense - Oates, Joyce Carol, 1938- (The Mysterious Press, 2021)
Presents nine tales of psyches puyshed to their limits by the expedtations of everyday life--from a woman who gets lost on her drive home to her plush suburban home and ends up breaking into a stranger's house, to a first-person account of a cloned 1940s magazine pinup girl being sold at auction and embodying America's ideals of beauty and womanhood.